IMPLEMENTATION OF ARIMA METHOD TO FORECAST CPI FOR COICOP OF FOOD, BEVERAGE AND TOBACCO IN NEW NORMAL PERIOD - Mahuda, Isnaini; Rahmawati, Septi Dwi; Sukmawati, Sri; Abdullah, Syarif (Jurnal Bayesian : Jurnal Ilmiah Statistika dan Ekonometrika, 2024)
CPI is one of the economic indicators that can provide information on development of prices for goods and services paid by consumers or the society, especially urban societies. CPI is usually used to measure price changes, but not to measure the price level. In addition, the CPI also can be used as a benchmark to determine inflation or deflation in a certain area. CPI value after the COVID-19 pandemic is the object to be predicted. There are 11 category in the CPI. This category is named COICOP which one of it is food, beverage and tobacco. The purpose of this research was to determine the ARIMA model to forecast the CPI value in the COICOP of food, beverage and tobacco in Banten Province. The data used is CPI data of COICOP for food, beverage and tobacco in Banten period January 2019 to April 2022. Based on these data obtained several prospective ARIMA models that passed the model diagnostic stage. The Models are ARIMA (0.3,1), ARIMA (1,3,0) and ARIMA (2,3,0) with MSE 1.1294, 1.9496 and 1.2484. The ARIMA (0.3.1) model was chosen because it has the smallest MSE value of 1.1294. Forecasting using the ARIMA (0.3.1) model obtained a significant increase in the CPI value from May to December 2022